(untitled) (International Journal of Engineering and Computer Science, 2016)
The electricity generation from many small resources is becoming one of the major systems in distribution generation systems to feed electrical loads. The effect of fault current and induced over voltages under abnormal conditions must be taken into account seriously. The effect of fault current can be limited by applying an active type superconducting fault current limiter (SFCL), the active SFCL is composed of an air-core superconducting transformer and a PWM converter. The magnetic field in the air-core can be controlled by adjusting the converters output current, and then the active SFCLs equivalent impedance can be regulated for current limitation and possible overvoltage suppression. During the study process, in view of the changes in the locations of the DG units connected to the system, the DG units injection capacities and the fault positions, the active SFCLs current-limiting and overvoltage suppressing characteristics are both simulated in MATLAB. The simulation results show that the active SFCL can play an important role in restraining the fault current and overvoltage, and it can contribute to avoiding damage on the relevant distribution equipment and improve the systems safety and reliability.